Análise da interação molecular proteína-herbicida através de simulação computacional: aplicação no desenvolvimento de nanobiossensores - Oliveira, Guedmiller Souza de (Universidade Federal de São Carlos, 2013)
In this study, our goal was evaluate the interactive forces between the Atomic force microscope tip (AFM tip) and an important enzyme responsible to fatty acids synthesis in all living beings (Acetyl CoA Carboxylase - fic biosensors to detect pesticides molecules used in agriculture. The AFM tip can be functionalized through its oxidation with spacer molecules. In order to simulate computationally this modified AFM tip that was called surface spacer-agent (SSA) using molecular dynamic (MD) simulations, the force field (FF) parameters had to be calculated. The FF parameters were obtained using quantum mechanical calculations and were implemented in an appropriate FF protocol. Three types of geometric molecular orientations of the ACCase were evaluated as a starting point to enzymatic immobilization, but only one was used to MD simulation. The criteria to define xyz orientation were basically based on the active sites from the ACCase enzyme are available to interact with molecules from the bulk and the surface contact area of the enzyme interacting with SSA ensure an strong interaction force to maintain the enzyme immobilized on the tip. Surface contact area, hydrogen bonds and protein stability were the parameters monitored during the MD trajectory as the enzymeherbicide interactions using a combination of molecular docking and molecular dynamics. The clusters formed using docking calculations in different regions along the ACCase enzyme were submitted to MD simulations in order to measure interactive energies of the system.
Analysis of the protein-herbicide interactions through computational simulation: application on the development of nanobiosensors
Keywords: Físico-química; Dinâmica molecular; Imobilização; Adsorção; Biosensores (Biossensores); Proteínas; Nanobiossensor; Imobilização enzimática; Simulação computacional; Modelo computacional; Nanobiosensor; Enzymatic immobilization; Computational simulation; Molecular dynamic; Adsorption; Computational model; CIENCIAS EXATAS E DA TERRA::QUIMICA